Behavior modification : - Martin, Garry (Prentice-Hall, 1978)
Behavior Modification: What It Is and How to Do It, 9e is addressed to two audiences: (a) college and university students taking courses in behavior modification, applied behavior analysis, behavior therapy, the psychology of learning, and related areas; and (b) students and practitioners of various helping professions (such as clinical psychology, counseling, education, medicine, nursing, occupational therapy, physiotherapy, psychiatric nursing, psychiatry, social work, speech therapy, and sport psychology) who are concerned directly with enhancing various forms of behavioral development.